Studies on the population dynamics of fruit flies (diptera: tephritidae) on mango orchards in Multan, Punjab, Pakistan - Abbas, Qaisar; Hasnain, Muhammad; Hussain, Mussurrat; Ali, Qurban; Jafir, Muhammad; Shahid, Muhammad; Iqbal, Muhammad; Abbas, Hasnain (Journal of Pure and Applied Agriculture, 2023)
Fruit flies (diptera: tephritidae) are considered as key pests of fruits and vegetables causing huge losses in yield and quality of the crops. Population dynamics of fruit flies was carried out by the use of methyl eugenol to investigate distribution and abundance in mango orchards. The experiment was carried out at farmer field in Multan. The population data was recorded from January, 2015 to December, 2016. Result indicated that overall maximum fruit flies catches were observed in pheromone trap i.e. 178.1 flies/trap followed by Bottle trap with 150.4 flies/trap. However, minimum fruit flies catches were observed in Jar trap with 90 flies/trap. Fruit flies infestation on mango started on 2nd week of February and it increased gradually with the passage of time and reached at peak level in the month of June which continued up to September. Then it showed decline in the months of October which continued until December when its population became zero. Data regarding meteorological factors showed the significant effects on fruit flies population. The temperature (minimum and maximum) show positive correlation with fruit flies population and temperature gradient showed negative correlation with fruit flies population. Similarly the humidity showed the negative correlation with fruit flies population. This study gives activity of the pest in Multan and approximate p